UTILIZZO DI NUOVI TEST IMMUNOLOGICI NELLA DIAGNOSTICA DELL’INFEZIONE E MALATTIA DA M.TUBERCULOSIS - I. Sauzullo; F. Mengoni; M. Lichtner; R. Rossi; V. Vullo; D. Vincenti; S. Carrara; D. Goletti; C.M. Mastroianni (Microbiologia Medica, 2005)
-